Correlation between disability, internalized stigma and mental recovery in patients with bipolar disorder - Yıldız, Elif Nur; Tarsuslu, Bedia; Durat, Gulgun (Frontiers in Psychology, 2025)
BackgroundThis study aimed to examine the correlation between disability, internalized stigma and mental recovery in patients with bipolar disorder. It further examined the impact of internalized stigma and disability on mental recovery.MethodsThe study was conducted with 103 patients diagnosed with bipolar disorder in remission who had been referred to a Community Mental Health Center. Data were collected using the Short Disability Assessment Schedule, Internalized Stigma of Mental Illness Scale and Recovery Process Inventory. Data were analyzed using an independent t-test, a one-way analysis of variance, and a multiple linear regression analysis.ResultsNo disability was diagnosed in 33.0% of the participants, while 25.2% had mild disability, 30.1% had moderate disability and 11.7% had severe disability. DAS-S scores indicated differences between the recovery process and internalized stigma scores (p < 0.05). While disability levels, alienation and perceived discrimination were not found to be effective on recovery, endorsement of stereotypes, social withdrawal, and resistance to stigma were found to be effective (F:43.343, p < 0.001, R2: 0.787).ConclusionThe prevalence of disability in patients with bipolar disorder increases the likelihood that these individuals will need more help from others. The mental recovery is positively affected by the endorsement of stereotypes, social withdrawal, and resistance to stigma.